Pop Culture and Spiritual Hybridity: New Sacred Figures in Thailand - Agarwal, Ruchi; Pongjit, Chompunuch (Thammasat Review, 2026)
The contemporary spiritual landscape of Thailand exhibits a trend of hybrid religiosity, wherein traditional beliefs coexist with new spiritual symbols derived from folklore, media, and material culture. This study investigates the emergence of Khru Kai Kaeo as a modern spiritual figure and contrasts it with the grotesque gargoyles of European Gothic architecture to evaluate how these symbols serve as cultural “shock absorbers” during periods of societal instability. The study applies a qualitative comparative methodology, including content analysis of media discourse, academic opinion, and public reactions to three current cultural phenomena: the Khru Kai Kaeo debate, the Buddha-Ultraman artworks, and the Optimus Prime monument. The results indicate that grotesque or hybrid spiritual forms are more prevalent in contexts marked by economic instability, heightened social competition, and the quest for emotional comfort. The study demonstrates that digital media platforms serve as new sacred spaces that facilitate the rapid transmission, commercialization, and recontextualization of spiritual practices. These observations enrich broader discussions on hybrid religiosity and the development of spiritual manifestations in modern Thailand.